High-strength concrete material prepared from desalted sea sand and preparation method of high-strength concrete material
The desalination of sea sand through a specific process and the use of other modified materials is solved by solving the problems of steel bar corrosion and unstable concrete performance caused by untreated sea sand, and high-strength concrete materials with high strength, durability and safety are achieved.
Patent Information
- Application Number
- CN202411731500.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, when untreated sea sand is used in concrete, the corrosion of the steel bars is intensified and the strength is reduced. The working performance of seawater concrete is unstable and the frost resistance is poor, and there is a risk of engineering accidents.
Desalinated sea sand through specific processes, including sea sand pre-sieve, freshwater purification, drying treatment, removing salt and impurities, and combining materials such as fine-ground shell powder, ultrafine manganese slag powder, polycarboxylic acid high-performance water reducer, chopped steel fibers and polymer resins to prepare high-strength concrete materials.
It significantly improves the durability and compressive strength of concrete, extends the service life of steel bars, improves the working performance and frost resistance of concrete, and reduces engineering risks.
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-strength concrete material preparation, in particular to a high-strength concrete material prepared by using desalinated sea sand and a preparation method thereof. Background Art
[0002] Sand is an important component of concrete. With the rapid development of the economy, the demand for concrete has gradually increased, and the demand for sand has also increased sharply. The contradiction between the supply and demand of river sand resources has become increasingly prominent. Excessive exploitation of river sand has caused serious damage to the environment. Compared with river sand, sea sand resources are abundant, well graded, and easy to mine. However, sea sand contains a large amount of chloride salts. If it is used directly without dechlorination, it will lead to the corrosion of steel bars in reinforced concrete structures. The continuous corrosion of steel bars will further reduce the strength of reinforced concrete, causing the peeling of the concrete protective layer or the cracking of steel bars. Unpurified sea sand can easily cause the steel bars in concrete to rust prematurely, burying serious quality risks for construction projects.
[0003] The patent application with publication number CN112028565A discloses a recycled coarse aggregate seawater and sea sand concrete and its preparation method and application, which includes a certain proportion of cement, natural coarse aggregate, sea sand, recycled coarse aggregate, seawater, fly ash, silica fume, additional water, and water reducing agent. By using a certain proportion of fly ash and fly ash as mineral admixtures to replace part of the cement, the durability and compressive and flexural strength of the recycled coarse aggregate concrete can be improved. By using recycled coarse aggregate to replace part of the natural coarse aggregate, construction waste can be fully recycled.
[0004] Due to the high mud content in untreated sea sand and the complex chemical substances in seawater, the direct use of seawater, sea sand and coral reefs to produce concrete has problems with unstable working performance and poor frost resistance. In addition, salts such as chlorides and sulfates, the main components of seawater, may cause seawater and sea sand concrete to set prematurely, which may affect concrete construction at the very least and may even cause engineering accidents in severe cases.
[0005] Therefore, the primary problem in using sea sand resources for construction is to desalinate the sea sand. Based on this, the present invention provides a high-strength concrete material prepared using desalinated sea sand. Summary of the invention
[0006] In order to solve the above problems existing in the prior art, the present invention provides a high-strength concrete material prepared using desalinated sea sand.
[0007] The technical solution adopted by the present invention to solve its technical problem is: A high-strength concrete material prepared using desalinated sea sand, the high-strength concrete material comprises the following material components: cement, fly ash, basalt aggregate, ultrafine manganese slag powder, silica fume, ground shell powder, polycarboxylic acid high-performance water reducer, desalinated sea sand, polymer resin, short-cut steel fiber, curing agent, concrete anti-corrosion and rust inhibitor and water. The mass fraction ratio of the material components is: 200-400 parts of cement, 50-100 parts of fly ash, 200-400 parts of basalt aggregate, 25-75 parts of ultrafine manganese slag powder, 20-40 parts of silica fume, 20-40 parts of ground shell powder, 5-10 parts of polycarboxylic acid high-performance water reducer, 200-400 parts of desalinated sea sand, 50-100 parts of polymer resin, 10-50 parts of short-cut steel fiber, 5-10 parts of curing agent, and 10-50 parts of concrete anti-corrosion and rust inhibitor.
[0008] A method for preparing a high-strength concrete material using desalinated sea sand comprises the following steps: (1) Preparation of desalinated sea sand.
[0009] (2) Preparation of finely ground shell powder.
[0010] (3) Pour cement, fly ash, basalt aggregate, silica fume, ground shell powder, desalinated sea sand, and curing agent into a forced mixer according to the mass fraction ratio and mix them evenly to obtain a mixture.
[0011] (4) Pour water and polymer resin into a forced mixer and start stirring to ensure that the materials are fully mixed. During the stirring process, gradually add ultrafine manganese slag powder, chopped steel fibers and polycarboxylic acid high-performance water reducer. Ultrafine manganese slag powder can increase the density of concrete, chopped steel fibers can significantly improve its crack resistance, and polycarboxylic acid high-performance water reducer helps to improve the fluidity of concrete. After these materials are fully mixed, add concrete anti-corrosion and rust inhibitor to further enhance the corrosion and rust resistance of concrete. Continue stirring to ensure that all ingredients are evenly distributed until the specified collapse is reached to obtain a high-strength concrete material slurry.
[0012] (5) Carefully place the steel bars in the prepared mold and ensure that they are fixed in place accurately. Use a high-strength concrete slurry and pour it evenly into the mold. During the pouring process, vibration molding is required to ensure that the concrete slurry can fully fill every corner of the mold and tightly combine with the steel bars. After the pouring and vibration molding are completed, the mold and the components in it are moved into a standard curing room.
[0013] (6) In a standard curing room, the concrete material is cured at a temperature of 35-45°C for 18-24 hours to ensure that the hydration reaction inside the concrete is fully carried out, thereby improving the early strength of the concrete. After the curing is completed, the concrete material is cured with hot water at 60-70°C for 40-50 hours to further promote the stability of the internal structure of the concrete and the improvement of its strength. After the curing is completed, the concrete material is taken out of the curing room and demolded to obtain the final high-strength concrete product.
[0014] The present invention also has the following additional technical features: As a further specific optimization of the technical solution of the present invention: the cement is G-grade oil well silicate cement.
[0015] As a further specific optimization of the technical solution of the present invention: the particle diameter of fly ash is 0.5-300mm, and its density is 2.0-2.9g / cm 3 , bulk density is 0.53-1.26g / cm 3 , with a specific surface area of 900-8000cm 2 / g, water absorption is 90%-130%.
[0016] As a further specific optimization of the technical solution of the present invention: the particle diameter of the basalt aggregate is 10-30 mm.
[0017] As a further specific optimization of the technical solution of the present invention: the particle size of the ultrafine manganese slag powder is 0.08-15μm, and the specific surface area is ≥1000m 2 / kg, 28d activity index ≥95%.
[0018] As a further specific optimization of the technical solution of the present invention: the density of silica fume is 2.2g / cm 3 The average particle size is 1 μm, and the specific surface area is between 15000-25000m 2 / kg.
[0019] As a further specific optimization of the technical solution of the present invention: the polycarboxylic acid high-performance water-reducing agent adopts a liquid water-reducing agent with a solid content of 20%, a total alkali content of 0.02%, a pH value of 7.0-8.0, and a water reduction rate of 26-35%.
[0020] As a further specific optimization of the technical solution of the present invention: the polymer resin is at least one of epoxy resin, phenolic resin, silicone resin and unsaturated polyester resin.
[0021] As a further specific optimization of the technical solution of the present invention: the chopped steel fiber is at least one of basalt fiber, glass fiber, steel fiber, polyethylene fiber and polypropylene fiber. The length of the chopped steel fiber is 5-30 mm.
[0022] As a further specific optimization of the technical solution of the present invention: the curing agent is at least one of an amine curing agent, an acid anhydride curing agent and a peroxide curing agent.
[0023] As a further specific optimization of the technical solution of the present invention: the concrete anticorrosion and rust inhibitor is sodium benzoate and at least two of sodium nitrite, calcium nitrite, sodium nitrite or calcium formate. The concrete anticorrosion and rust inhibitor is a composite rust inhibitor, which is used in combination with multiple rust-inhibiting components to improve its comprehensive effect by using synergistic effect.
[0024] As a further specific optimization of the technical solution of the present invention: Desalinated sea sand is prepared according to the following steps: (1) Sea sand pre-screening: The sea sand is extracted by using an ocean sand pumping vessel. The sea sand is pre-screened through a vibrating screen to remove shells and gravel and obtain sea sand with a particle size of less than 5 mm.
[0025] (2) Sea sand and fresh water purification: The screened sea sand enters the spiral sand washing machine, into which fresh water or desalinated seawater is added, and activated carbon and flocculants are added. Activated carbon is an adsorbent based on physical adsorption and chemical reaction. Its microporous structure can provide a large amount of adsorption surface. The chemically active sites on the surface of the adsorbent can also react with some chemical substances to further improve the adsorption performance. In this step, activated carbon can remove organic matter, odor, residual chlorine and some heavy metal ions dissolved in water. Flocculants can precipitate most of the bacteria, algae, tiny particulate matter and flocs formed by flocculation in the wastewater. Start the spiral sand washing machine and stir at room temperature for 3-5 hours.
[0026] (3) Separation: The sea sand treated with sea sand desalination in step (2) is subjected to secondary filtration to remove flocculant precipitate and activated carbon, thereby obtaining water-containing desalinated sea sand.
[0027] (4) Drying treatment: The water-containing desalinated sea sand obtained in step (3) is heated at 150-180° C. for 1-1.5 h to obtain finished desalinated sea sand.
[0028] As a further specific optimization of the technical solution of the present invention: Preparation method of ground shell powder, (1) Take shells and conch shells, including oyster shells, scallop shells, pearl shells or oyster shells. Use a high-pressure water spray gun to high-pressure wash the shells and conch shells for 5-10 minutes, and then dry them in the air or place them in a dryer at a temperature of 25-30℃ for drying.
[0029] (2) The dried shells and conch shells are placed in a roasting furnace and roasted at 800-900°C for 2-3 hours to completely decompose the organic matter in the shells and conch shells and convert them into calcium oxide and other minerals.
[0030] (3) After roasting, the shells and conch shells are taken out, cooled, and then ground using a ball mill until the fineness reaches 1000±250 mesh to obtain high-purity calcium carbonate fine powder.
[0031] (4) Finally, the ground calcium carbonate powder is screened to ensure that there are no large particles of impurities, and the chloride ion content is tested to ensure that the free chloride ion content is less than 0.03% to meet the preparation requirements of high-strength concrete materials.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] Advantage 1: The present invention uses a specific process to treat desalinated sea sand to meet the quality requirements for preparing high-strength concrete. Desalinated sea sand is purified by a combination of physical and chemical methods to remove salt, organic matter and other impurities. During the purification process, the sea sand is first washed with water to remove salt and impurities on the surface, and then the chloride ion content in the sea sand is further reduced by physical and chemical methods to ensure that it meets the use standards of concrete materials.
[0034] Advantage 2: The present invention adopts a specific method for preparing finely ground shell powder, and uses finely ground shell powder to replace part of the cement, which can effectively improve the compressive strength and durability of concrete. The preparation process of finely ground shell powder is simple and easy to mass produce, which provides a new way for the sustainable development of concrete materials. It also utilizes marine waste, has environmental protection significance, and reduces the cost of concrete materials.
[0035] Advantage 3: High-strength concrete materials prepared using desalinated sea sand have obvious advantages in performance, especially in durability and strength, and also have significant advantages in resource utilization and environmental protection. DETAILED DESCRIPTION Example 1
[0036] The high-strength concrete material is prepared using desalinated sea sand, and the high-strength concrete material includes the following material components: cement, fly ash, basalt aggregate, ultrafine manganese slag powder, silica fume, ground shell powder, polycarboxylic acid high-performance water reducing agent, desalinated sea sand, polymer resin, chopped steel fiber, curing agent, concrete anti-corrosion and rust inhibitor and water.
[0037] The cement is G-grade oil well silicate cement, which is particularly suitable for applications in special environments such as oil wells due to its excellent high temperature resistance and compressive strength.
[0038] The particle diameter of fly ash is 0.5-300mm and its density is 2.0-2.9g / cm 3 , bulk density is 0.53-1.26g / cm 3 , with a specific surface area of 900-8000cm 2 / g, and the water absorption is 90%-130%. As an industrial by-product, fly ash has good filling and water-reducing effects, and can significantly improve the working performance and durability of concrete.
[0039] The particle diameter of basalt aggregate is 10-30mm; basalt aggregate is often used in concrete to improve its overall performance due to its high strength and wear resistance.
[0040] The particle size of ultrafine manganese slag powder is 0.08-15μm, and the specific surface area is ≥1000m 2 / kg, 28d activity index ≥95%; ultrafine manganese slag powder, as an industrial waste, is prepared by ultrafine grinding and has high activity, which can effectively improve the strength and durability of concrete.
[0041] The density of silica fume is 2.2g / cm 3 The average particle size is 1 μm, and the specific surface area is between 15000-25000m 2 / kg; Silica fume, as a highly active mineral admixture, can significantly improve the impermeability and durability of concrete.
[0042] Polycarboxylic acid high-performance water-reducing agent uses liquid water-reducing agent with a solid content of 20%, a total alkali content of 0.02%, a pH value of 7.0-8.0, and a water reduction rate of 26-35%; this water-reducing agent can effectively reduce the water-cement ratio of concrete and improve its workability and strength.
[0043] The polymer resin is at least one of epoxy resin, phenolic resin, silicone resin and unsaturated polyester resin; these resins have excellent chemical corrosion resistance and mechanical properties and are often used in the modification of concrete to improve its durability and crack resistance.
[0044] The chopped steel fiber is at least one of basalt fiber, glass fiber, steel fiber, polyethylene fiber and polypropylene fiber; the length of the chopped steel fiber is 5-30 mm; the chopped steel fiber can significantly improve the crack resistance and impact resistance of concrete.
[0045] The curing agent is at least one of an amine curing agent, an acid anhydride curing agent and a peroxide curing agent; these curing agents can accelerate the curing process of the resin and improve the mechanical properties and durability of the concrete.
[0046] The concrete anti-corrosion and rust inhibitor is sodium benzoate and at least two of sodium nitrite, calcium nitrite, sodium nitrite or calcium formate; the concrete anti-corrosion and rust inhibitor is a composite rust inhibitor, which is used in combination with multiple rust-inhibiting ingredients and utilizes synergistic effects to improve its comprehensive effect, thereby effectively preventing the steel bars in the concrete from rusting and extending their service life. Example 2
[0047] In Example 1, desalinated sea sand was prepared according to the following steps: (1) Sea sand pre-screening: The sea sand is extracted by using an ocean sand pumping vessel. The sea sand is pre-screened through a vibrating screen to remove shells and gravel and obtain sea sand with a particle size of less than 5 mm.
[0048] (2) Sea sand and fresh water purification: The screened sea sand enters the spiral sand washing machine, into which fresh water or desalinated seawater is added, and activated carbon and flocculants are added; activated carbon is an adsorbent based on physical adsorption and chemical reaction. Its microporous structure can provide a large amount of adsorption surface. The chemically active sites on the adsorbent surface can also react with some chemical substances to further improve the adsorption performance. In this step, activated carbon can remove organic matter, odor, residual chlorine and some heavy metal ions dissolved in water. Flocculants can precipitate most of the bacteria, algae, tiny particulate matter and flocs formed by flocculation in the wastewater. Start the spiral sand washing machine and stir at room temperature for 3-5 hours.
[0049] (3) Separation: The sea sand treated with sea sand desalination in step (2) is subjected to secondary filtration to remove flocculant precipitate and activated carbon, thereby obtaining water-containing desalinated sea sand.
[0050] (4) Drying treatment: The water-containing desalinated sea sand obtained in step (3) is heated at 150-180° C. for 1-1.5 h to obtain finished desalinated sea sand. Example 3
[0051] In Example 1, the preparation method of ground shell powder is: (1) Take shells and conch shells, including oyster shells, scallop shells, pearl shells or oyster shells; use a high-pressure water spray gun to high-pressure wash the shells and conch shells for 5-10 minutes, dry them after high-pressure washing, or place them in a dryer at a temperature of 25-30°C for drying.
[0052] (2) The dried shells and conch shells are placed in a roasting furnace and roasted at 800-900°C for 2-3 hours to completely decompose the organic matter in the shells and conch shells and convert them into calcium oxide and other minerals.
[0053] (3) After roasting, the shells and conch shells are taken out, cooled, and then ground using a ball mill until the fineness reaches 1000±250 mesh to obtain high-purity calcium carbonate fine powder.
[0054] (4) Finally, the ground calcium carbonate powder is screened to ensure that there are no large particles of impurities, and the chloride ion content is tested to ensure that the free chloride ion content is less than 0.03% to meet the preparation requirements of high-strength concrete materials. The present invention adopts a specific preparation method of ground shell powder, and uses the ground shell powder to replace part of the cement, which can effectively improve the compressive strength and durability of concrete. The preparation process of the ground shell powder is simple and easy to mass produce, which provides a new way for the sustainable development of concrete materials, utilizes marine waste, has environmental protection significance, and reduces the cost of concrete materials. Example 4
[0055] The high-strength concrete material prepared using desalinated sea sand based on Examples 1-3, the preparation method comprises the following steps: (1) preparing desalinated sea sand (see Example 2); (2) preparing ground shell powder (Example 3); (3) Pour cement, fly ash, basalt aggregate, silica fume, ground shell powder, desalinated sea sand, and curing agent into a forced mixer according to the mass fraction ratio and mix them evenly to obtain a mixture.
[0056] (4) Pour water and polymer resin into a forced mixer and start stirring to ensure that the materials are fully mixed; during the stirring process, gradually add ultrafine manganese slag powder, chopped steel fibers and polycarboxylic acid high-performance water reducer; ultrafine manganese slag powder can increase the density of concrete, chopped steel fibers can significantly improve its crack resistance, and polycarboxylic acid high-performance water reducer helps to improve the fluidity of concrete; after these materials are fully mixed, add concrete anti-corrosion and rust inhibitor to further enhance the corrosion and rust resistance of concrete; continue stirring to ensure that all components are evenly distributed until the specified collapse degree is reached to obtain a high-strength concrete material slurry.
[0057] (5) Carefully place the steel bars in the prepared mold and ensure that they are fixed in place accurately. Use a high-strength concrete slurry to evenly pour it into the mold. During the pouring process, vibration molding is required to ensure that the concrete slurry can fully fill every corner of the mold and is tightly combined with the steel bars. After pouring and vibration molding are completed, move the mold together with the components in it into a standard curing room.
[0058] (6) In a standard curing room, the concrete material is cured at a temperature of 35-45°C for 18-24 hours to ensure that the hydration reaction inside the concrete is fully carried out, thereby improving the early strength of the concrete. After the curing is completed, the concrete material is cured with hot water at 60-70°C for 40-50 hours to further promote the stability of the internal structure of the concrete and the improvement of its strength. After the curing is completed, the concrete material is taken out of the curing room and demolded to obtain the final high-strength concrete product.
[0059] The present invention uses a specific process to treat desalinated sea sand so that it meets the quality requirements for preparing high-strength concrete. Desalinated sea sand is purified by combining physical and chemical methods to remove salt, organic matter and other impurities therein. During the purification process, the sea sand is first washed with water to remove salt and impurities on the surface, and then the chloride ion content in the sea sand is further reduced by physical and chemical methods to ensure that it meets the use standards of concrete materials. Example 5
[0060] The preparation method of the high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 200 parts of cement, 50 parts of fly ash, 200 parts of basalt aggregate, 25 parts of ultrafine manganese slag powder, 20 parts of silica fume, 20 parts of ground shell powder, 5 parts of polycarboxylic acid high-performance water reducer, 200 parts of desalinated sea sand, 50 parts of polymer resin, 10 parts of chopped steel fiber, 5 parts of curing agent, and 10 parts of concrete anti-corrosion and rust inhibitor. Example 6
[0061] The preparation method of the high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 400 parts of cement, 100 parts of fly ash, 400 parts of basalt aggregate, 75 parts of ultrafine manganese slag powder, 40 parts of silica fume, 40 parts of ground shell powder, 10 parts of polycarboxylic acid high-performance water reducing agent, 400 parts of desalinated sea sand, 100 parts of polymer resin, 50 parts of chopped steel fiber, 10 parts of curing agent, and 50 parts of concrete anti-corrosion and rust inhibitor. Example 7
[0062] The preparation method of high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 280 parts of cement, 70 parts of fly ash, 280 parts of basalt aggregate, 45 parts of ultrafine manganese slag powder, 28 parts of silica fume, 28 parts of ground shell powder, 6 parts of polycarboxylic acid high-performance water reducer, 280 parts of desalinated sea sand, 65 parts of polymer resin, 25 parts of chopped steel fiber, 7 parts of curing agent, and 25 parts of concrete anti-corrosion and rust inhibitor. Example 8
[0063] The preparation method of high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 320 parts of cement, 85 parts of fly ash, 320 parts of basalt aggregate, 65 parts of ultrafine manganese slag powder, 32 parts of silica fume, 32 parts of ground shell powder, 8 parts of polycarboxylic acid high-performance water reducer, 320 parts of desalinated sea sand, 80 parts of polymer resin, 45 parts of chopped steel fiber, 8 parts of curing agent, and 45 parts of concrete anti-corrosion and rust inhibitor. Comparative Example 1
[0064] The preparation method of high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 320 parts of cement, 85 parts of fly ash, 65 parts of ultrafine manganese slag powder, 32 parts of silica fume, 32 parts of ground shell powder, 8 parts of polycarboxylic acid high-performance water reducer, 320 parts of desalinated sea sand, 80 parts of polymer resin, 8 parts of curing agent, and 45 parts of concrete anti-corrosion and rust inhibitor. Comparative Example 2
[0065] The preparation method of the high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 200 parts of cement, 50 parts of fly ash, 200 parts of basalt aggregate, 25 parts of ultrafine manganese slag powder, 20 parts of silica fume, 20 parts of ground shell powder, 5 parts of polycarboxylic acid high-performance water reducing agent, 200 parts of river sand, 50 parts of polymer resin, 10 parts of chopped steel fiber, and 5 parts of curing agent. Comparative Example 3
[0066] The preparation method of the high-strength concrete material adopts Example 4, wherein the high-strength concrete material is prepared using desalinated sea sand, and the mass fraction ratio of the components of the high-strength concrete material is: 200 parts of cement, 50 parts of fly ash, 200 parts of basalt aggregate, 25 parts of ultrafine manganese slag powder, 20 parts of silica fume, 5 parts of polycarboxylic acid high-performance water reducing agent, 200 parts of desalinated sea sand, 10 parts of chopped steel fiber, and 5 parts of curing agent. In Comparative Example 2, river sand was replaced with desalinated sea sand, and no concrete anticorrosion and rust inhibitor was added. From the above data, it can be seen that the high-strength concrete materials of Examples 5 to 8 are not much different from those of Comparative Example 2 in terms of performance indicators such as machine slump, 30-minute slump, initial setting time, final setting time, and 1-day, 7-day, and 28-day compressive strength, which shows that the effect of the desalinated sea sand of the present invention is not much different from that of river sand, and that the concrete anticorrosion and rust inhibitor has the effect of preventing concrete from rusting.
[0067] In Comparative Examples 1 and 3, the components of the concrete materials were reduced respectively. From the above data, it can be seen that the high-strength concrete materials of Examples 5 to 8 are superior to Comparative Examples 1 and 3 in performance indicators such as slump out of the machine, slump after 30 minutes, initial setting time, final setting time, and compressive strength after 1 day, 7 days and 28 days.
[0068] Through comparative analysis, it can be concluded that high-strength concrete materials prepared using desalinated sea sand have obvious advantages in performance, especially in durability and strength, and also have significant advantages in resource utilization and environmental protection.
Claims
1. A high-strength concrete material prepared using desalinated sea sand, characterized in that: The high-strength concrete material includes the following material components: cement, fly ash, basalt aggregate, ultrafine manganese slag powder, silica fume, ground shell powder, polycarboxylic acid high-performance water reducing agent, desalinated sea sand, polymer resin, chopped steel fiber, curing agent, concrete anti-corrosion and rust inhibitor and water; wherein: the mass fraction ratio of the material components is: 200-400 parts of cement, 50-100 parts of fly ash, 200-400 parts of basalt aggregate, 25-75 parts of ultrafine manganese slag powder, 20-40 parts of silica fume, 20-40 parts of ground shell powder, 5-10 parts of polycarboxylic acid high-performance water reducing agent, 200-400 parts of desalinated sea sand, 50-100 parts of polymer resin, 10-50 parts of chopped steel fiber, 5-10 parts of curing agent, and 10-50 parts of concrete anti-corrosion and rust inhibitor.
2. The high-strength concrete material prepared using desalinated sea sand according to claim 1, characterized in that: The cement is Grade G oil well silicate cement; The particle diameter of the fly ash is 0.5-300 mm, and its density is 2.0-2.9 g / cm 3 , bulk density is 0.53-1.26g / cm 3 , with a specific surface area of 900-8000cm 2 / g, water absorption is 90%-130%; The particle diameter of the basalt aggregate is 10-30 mm; The ultrafine manganese slag powder has a particle size of 0.08-15 μm and a specific surface area of ≥1000 m 2 / kg, 28d activity index ≥95%; The density of the silica fume is 2.2 g / cm 3 The average particle size is 1 μm, and the specific surface area is between 15000-25000m 2 / kg; The polycarboxylic acid high-performance water reducer adopts a liquid water reducer with a solid content of 20%, a total alkali content of 0.02%, a pH value of 7.0-8.0, and a water reduction rate of 26-35%; The polymer resin is at least one of epoxy resin, phenolic resin, silicone resin and unsaturated polyester resin; The chopped steel fiber is at least one of basalt fiber, glass fiber, steel fiber, polyethylene fiber and polypropylene fiber; the length of the chopped steel fiber is 5-30 mm; The curing agent is at least one of an amine curing agent, an acid anhydride curing agent and a peroxide curing agent; The concrete anti-corrosion and rust inhibitor is at least two of sodium benzoate and sodium nitrite, calcium nitrite, sodium nitrite or calcium formate.
3. The high-strength concrete material prepared using desalinated sea sand according to claim 1, characterized in that: The desalinated sea sand is prepared according to the following steps: (1) Sea sand pre-screening: Use an ocean sand pumping ship to extract sea sand, and pre-screen the sea sand through a vibrating screen to remove shells and gravel, and obtain sea sand with a particle size of less than 5 mm; (2) Sea sand and fresh water purification: The screened sea sand enters the spiral sand washing machine, into which fresh water or desalinated seawater is added, and activated carbon and flocculants are added; the spiral sand washing machine is started and stirred at room temperature for 3-5 hours; (3) Separation: The sea sand treated with sea sand desalination in step (2) is subjected to secondary filtration to remove flocculant precipitate and activated carbon, thereby obtaining water-containing desalinated sea sand; (4) Drying treatment: The water-containing desalinated sea sand obtained in step (3) is heated at 150-180° C. for 1-1.5 h to obtain finished desalinated sea sand.
4. The high-strength concrete material prepared using desalinated sea sand according to claim 1, characterized in that: The preparation method of the ground shell powder, (1) Take shells and conch shells, including oyster shells, scallop shells, pearl shells or oyster shells; use a high-pressure water spray gun to high-pressure wash the shells and conch shells for 5-10 minutes, dry them after high-pressure washing, or place them in a dryer at a temperature of 25-30°C for drying; (2) placing the dried shells and conch shells into a roasting furnace and roasting them at 800-900°C for 2-3 hours to completely decompose the organic matter in the shells and conch shells and convert them into calcium oxide and other minerals; (3) After roasting, the shells and conch shells are taken out, cooled, and then ground using a ball mill until the fineness reaches 1000±250 mesh to obtain high-purity calcium carbonate fine powder; (4) Finally, the ground calcium carbonate powder is screened to ensure that there are no large particles of impurities, and the chloride ion content is tested to ensure that the free chloride ion content is less than 0.03% to meet the preparation requirements of high-strength concrete materials.
5. A method for preparing high-strength concrete material using desalinated sea sand, characterized in that: The following steps are involved: (1) Preparation of desalinated sea sand; (2) preparing finely ground shell powder; (3) Pour cement, fly ash, basalt aggregate, silica fume, ground shell powder, desalinated sea sand, and curing agent into a forced mixer according to the mass fraction ratio and mix them evenly to obtain a mixture; (4) Pour water and polymer resin into a forced mixer and start stirring to ensure that the materials are fully mixed; during the stirring process, gradually add ultrafine manganese slag powder, chopped steel fiber and polycarboxylic acid high-performance water reducer; after these materials are fully mixed, add concrete anticorrosion and rust inhibitor; continue stirring to ensure that all ingredients are evenly distributed until the specified collapse degree is reached to obtain a high-strength concrete material slurry; (5) Carefully place the steel bars in the prepared mold and ensure that they are fixed in place accurately; use a high-strength concrete slurry to evenly pour it into the mold; during the pouring process, vibration molding is required; after the pouring and vibration molding are completed, move the mold together with the components in it into a standard curing room; (6) In a standard curing room, the concrete material is cured at a temperature of 35-45°C for 18-24 hours to ensure that the hydration reaction inside the concrete is fully carried out, thereby improving the early strength of the concrete; after the curing is completed, the concrete material is cured using hot water at 60-70°C for 40-50 hours. After the curing is completed, the concrete material is taken out of the curing room and demolded to obtain the final high-strength concrete product.
Citation Information
Patent Citations
Recycled coarse aggregate seawater sea sand concrete as well as preparation method and application thereof
CN112028565A
Cited By
Seawater sea sand concrete with dispersion resistance and ductility and preparation method thereof
CN120483644A